1998
DOI: 10.2337/diacare.21.4.549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Glucose Intolerance Among Native Hawaiians in Two Rural Communities

Abstract: This study observed a high prevalence of glucose intolerance associated with being overweight among native Hawaiians. Age-adjusted type 2 diabetes prevalence was four times higher than among the U.S. National Health and Nutrition Examination Survey (NHANES) II population. Prevalence was high despite high rates of admixture with other ethnic groups of Hawaii, suggesting that these other Asian and Pacific Island populations share similar susceptibility to type 2 diabetes risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…These findings contrast somewhat with the NHHR project's earlier report that age-adjusted prevalence of glucose intolerance was not significantly associated with Native Hawaiian ancestry. 16 There are several possible explanations for this apparent contradiction. In our earlier report, collapsing of continuous variables (fasting and 2 h glucose concentrations) into a single categorical variable (glucose tolerance status) may have resulted in a loss of statistical information and a subsequent loss of statistical power.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These findings contrast somewhat with the NHHR project's earlier report that age-adjusted prevalence of glucose intolerance was not significantly associated with Native Hawaiian ancestry. 16 There are several possible explanations for this apparent contradiction. In our earlier report, collapsing of continuous variables (fasting and 2 h glucose concentrations) into a single categorical variable (glucose tolerance status) may have resulted in a loss of statistical information and a subsequent loss of statistical power.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the use of a summary measure such as glucose tolerance status determined by 2 h OGTT may have obscured the association between Hawaiian ancestry and plasma glucose levels in previous reports. 16 Thus, admixture with ethnic groups in which beta-cell defects may be prevalent and highly inheritable 29 may independently contribute to the high prevalence of type 2 diabetes observed among Native Hawaiians with multiethnic ancestry. It is uncertain whether these differences reflect genetic or culturally determined behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hawaii (HI)-The Native Hawaiian Health Research Project, a population-based, crosssectional study to determine the association between cardiovascular risk factors, glucose intolerance, insulin resistance, and ethnicity, conducted a multi-ethnic study from 1997 to 2001 [1,20]. Participants included a comparison cohort of Filipinos, ≥18 years of age, who were recruited from a rural community (North Kohala) on the island of Hawaii, using census data for door-to-door sampling.…”
Section: Study Populationmentioning
confidence: 99%
“…Ethnic disparities in type 2 diabetes prevalence in the United States (US) have been attributed to ethnic differences in adiposity [1][2][3][4][5]. Epidemiologic studies of immigrant populations have shown an increased risk of type 2 diabetes associated with the adoption of a western diet and lifestyle [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%